Ergometric ratio and time vs distance in the estimation of anaerobic capacity in top class 400m running athlete - Gabrys, T. (2001)
The precise analysis of work parameters achieved during sprint running focusing mainly on the ergometric ratio: "time vs distance". This approach provides valuable information about the precise nature of metabolic processes fuelling this sort of exercise. In track-and-field running, alternations of the amounts of total work performed during sprint running may be expressed by the equation: S=a+b´ t /S-the length of distance, a-section of distance fuelled by means of reserve metabolic process, b-horizontal velocity corresponding to the greatest intensification of the main metabolism, t-distance coverage time. According to the above equation, total work obtained during running on a distance consists of two integrants: work performed by means of reserve energy sources (coefficient - a), work in which energy is derived mainly from principal metabolic process (product: b´ t). Ergometric relationships between time and distance, calculated from the personal best of an elite Polish athlete in the 400m (P.H. - 1996 Olympic Games finalist and 1998 European and 1999 World Championships medalist), are exemplified in table. In the first range of work relating to maximal anaerobic power horizontal velocity in the 100 m is considerably below the one developed in the 150m. Similarly, the results in the 200m and 300m differ from the line of marks made by joining the personal bests in the 150 m and 400m. In the scope of submaximal power (distances from 350m on) the marks of his personal bests reflect his maximal abilities. The obtained values, in the course of ergometric analysis, may be used as indicators of regular control of exercise adaptation processes in highly qualified athletes. Table 1. P.H`s Personal Best Achieved in Distances Running from 40m to 500m